Systems approach to model smart tourism ecosystems - Sedarati, Pooyan (2022)
The tourism industry is inherently complex and a key player in sustainable development. This paper intends to discuss the path towards building a sustainable smart tourism ecosystem model by delving deep into the pivotal topics with interesting speculations on smart cities' perspectives that lay a broader foundation of smart tourism destinations. First, it discusses the interconnections and foundation of smart tourism ecosystems by proposing a general conceptual model describing traditional tourism transformation through ICTs. Second, by explicating each building block of smart tourism ecosystems and using systems methodology (systems thinking method and qualitative modeling in a frame of system dynamics) to break down the complex system of smart tourism's roles and components. Such methods are widely utilized in different fields of study to facilitate the decisionmaking process by furnishing a holistic view of the problem. For that matter, Causal Loop Diagramming (CLDs) was used as one of the powerful tools of systems thinking to depict smart tourism ecosystems. The proposed causal loop diagram considers sustainability as one of the main concerns and trying to shed some light on intricate networks of businesses, socioeconomic, and environmental subsystems in smart tourism destinations that are performing distinctively yet interdependent. This study is an ongoing process employing System Dynamics (SD) methodology for model testing and validation.